2021
DOI: 10.1088/1361-6595/abff10
|View full text |Cite
|
Sign up to set email alerts
|

Ion heating in the PISCES-RF liquid-cooled high-power, steady-state, helicon plasma device

Abstract: Radio frequency (RF) driven helicon plasma sources are commonly used for their ability to produce high-density argon plasmas (n > 1019 m−3) at relatively moderate powers (typical RF power < 2 kW). Typical electron temperatures are <10 eV and typical ion temperatures are <0.6 eV. A newly designed helicon antenna assembly (with concentric, double-layered, fully liquid-cooled RF-transparent windows) operates in steady-state at RF powers up to 10 kW. We report on the dependence of argon plasma density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…We also find that in the core plasma, direct collisional effects are more dominant, primarily due to the very high densities. Measurements of the ion temperature in argon plasma, using LIF [42], are consistent with results of a 0-D, volumeaveraged global model where collisional heating is balanced by diffusive radial losses and convective end losses. Hence it seems that near the core, collisional heating is the dominant heating mechanism.…”
Section: Conclusion and Additional Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We also find that in the core plasma, direct collisional effects are more dominant, primarily due to the very high densities. Measurements of the ion temperature in argon plasma, using LIF [42], are consistent with results of a 0-D, volumeaveraged global model where collisional heating is balanced by diffusive radial losses and convective end losses. Hence it seems that near the core, collisional heating is the dominant heating mechanism.…”
Section: Conclusion and Additional Discussionsupporting
confidence: 73%
“…Hence it seems that near the core, collisional heating is the dominant heating mechanism. In addition, measurements of the radial profiles of the electron temperature shows an elevated contribution near the edge [42], where the effect of the Trivelpiece-Gould (T-G) mode is expected to be maximum. Preliminary modeling of our device using COMSOL also shows this enhanced energy absorption by the electrons in this spatial region.…”
Section: Conclusion and Additional Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source parameters used in the estimation are listed in Table 3. It was found that the axial model was able to predict the behavior of the axial density profile, Comparison of the radial plasma density distribution estimated by Ahedo's radial model [12,20] and experimental data published by Burin et al [21], Castro et al [22], and Thakur et al [5,23].…”
Section: Model Validationmentioning
confidence: 99%
“…The chosen versions of these models are the asymptotic, magnetized regimes. For the case of the radial model [12,20], Figure 3 shows the normalized radial profile of the plasma density, compared to experimental data from the CSDX device published by Burin et al [21], from the VX-CR device by Castro et al [22] and from the PISCES-RF device by Thakur et al [5,23], from experimental runs using argon gas as the feedstock in all cases. The published experimental parameters obtained from these experimental data sets are described in Table 2.…”
Section: Model Validationmentioning
confidence: 99%